2002
DOI: 10.1042/0264-6021:3610613
|View full text |Cite
|
Sign up to set email alerts
|

S′2 substrate specificity and the role of His110 and His111 in the exopeptidase activity of human cathepsin B

Abstract: The ability of the lysosomal cysteine protease cathepsin B to function as a peptidyldipeptidase (removing C-terminal dipeptides) has been attributed to the presence of two histidine residues (His(110) and His(111)) present in the occluding loop, an extra peptide segment located in the primed side of the active-site cleft. Whereas His(111) is unpaired, His(110) is present as an ion pair with Asp(22) on the main body of the protease. This ion pair appears to act as a latch to hold the loop in a closed position. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 46 publications
2
56
0
Order By: Relevance
“…In agreement with published data (Illy et al 1997;Nägler et al 1997;Quraishi et al 1999;Krupa et al 2002) our results support the notion that the occluding loop of cathepsin B is a highly flexible segment. Short episodes of opening and closing govern endo-and exoproteolysis, which thus occur intermittently in the pH range 4.5-6.0.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In agreement with published data (Illy et al 1997;Nägler et al 1997;Quraishi et al 1999;Krupa et al 2002) our results support the notion that the occluding loop of cathepsin B is a highly flexible segment. Short episodes of opening and closing govern endo-and exoproteolysis, which thus occur intermittently in the pH range 4.5-6.0.…”
Section: Discussionsupporting
confidence: 83%
“…At low pH, two salt bridges, His 110 -Asp 22 and Arg 116 -Asp 224 , hold the loop in a closed position over the primed subsites of the substrate binding cleft, thus preventing extended binding of polypeptides and endoproteolytic activity. The closed conformation, through the engagement of His 111 in a hydrogen bond with the Cterminal carboxylate of the substrate and the loose specificity in P29, is responsible for the peptidyl-dipeptidase activity of cathepsin B (Illy et al 1997;Quraishi et al 1999;Krupa et al 2002). As mutations of the amino acids His 110 and Asp 22 have shown, removal of the salt bridges induces endopeptidase activity, attributed to increased flexibility of the loop (Nägler et al 1997).…”
mentioning
confidence: 99%
“…Sequence comparison with human cathepsin B revealed that SmCB1 has the predicted occluding loop, which has been shown to confer exopeptidase (specifically peptidyl dipeptidase) activity in vertebrate cathepsin Bs [37]. A novel assay for such activity was developed and confirmed that SmCB1 acts as an exopeptidase in addition to its endopeptidolytic activity described herein and elsewhere.…”
Section: Discussionmentioning
confidence: 81%
“…The conserved cysteine residues and the amino acids comprising the occluding loop (required for the exopeptidase activity of cathepsin B) are present. However, of the two key His residues that are required for exopeptidase activity (110 and 111 in the human sequence [25]), only one is present in the Fasciola proteins (amino acid 109 in the mature protein, corresponding to amino acid 110 in mature human cathepsin B). In each of the remaining species represented in Fig.…”
Section: Resultsmentioning
confidence: 99%